Aptamers for biosensors - Bini, Alessandra (Cranfield University and University of Firenze., 2008)
Aptamers are single-stranded DNA or RNA molecules isolated in vitro by a selection and amplification method. Aptamers bind with high specificity and affinity to a wide range of target molecules, with dissociation constant comparable to antibodies. In this work aptamers were employed as a new kind of bio-recognition element in affinity biosensors for the detection of clinically relevant proteins in heterogeneous assay, using Piezoelectric Quartz Crystal Microbalance and Surface Plasmon Resonance as transducers. The work was focused on two case studies, i.e. the Thrombin-binding aptamer and the aptamer against C-Reactive Protein. From an analytical point of view, the work was devoted to the optimisation of the analytical performance of a piezoelectric and an optical aptasensor for Thrombin and C-Reactive Protein detection, respectively. Efforts towards the application of these aptasensors in complex matrices, such as human plasma and serum, were also undertaken, in order to demonstrate the wide applicability of aptamers, as an alternative to antibodies. In this work, the possibility of introducing a computationally-assisted method to study aptamer-protein interaction and aptamer selection was also evaluated. For this purpose, the Thrombin-binding aptamer was chosen as a model and a retrospective docking study was performed by comparing the affinity of mutated sequences for thrombin with that of the Thrombin-binding aptamer, on the basis of a computationally-derived binding score. Finally, the reliability of computational results was tested by experimental measurements. For this purpose, the Thrombin-binding aptamer and other mutated sequences, selected on the basis of their binding score, were employed for the development of optical biosensors and the resulting analytical performances were compared. Even if further studies should be carried out in order to validate the proposed computational approach to aptamer selection, this work can have a significant impact on future aptamers selection for sensors and diagnostics.